Episcleral circular buckling: yesterday, today, and tomorrow - A. V. Tereshchenko; I. G. Trifanenkova; O. S. Kulikov; N. N. Yudina; Yu. A. Sidorova; M. A. Plakhotniy (Российский офтальмологический журнал)
Searching for methods of treating primary rhegmatogenous retinal detachment (RRD) is a highly relevant issue, since this disease often leads to disability in people of young working age. The history of surgical treatment of retinal detachment began more than 200 years ago and has undergone many changes due to the evolution of knowledge of this disease. In the early 20th century, sealing of retinal breaks was first shown to be a key principle in the treatment of RRD. The two most commonly used surgical techniques today are pars plana vitrectomy and scleral buckling. Over the years, various materials have been studied as possible buckling means. At present, soft silicone fine-pored tape is the gold standard for scleral sealing. Modern laser technologies open up new vistas for extrascleral surgery in the treatment of primary RRD. The advantages of specific individual approaches or combinations thereof are under active discussion.